AN ANALYSIS OF FIGURATIVE LANGUAGE IN AVRIL LAVIGNE SONGS IN ALBUM AVRIL LAVIGNE - Abdulloh abdulloh; ugi rahayu rahmawati (Journal of English Language and Literature (JELL), 2018)
This research aims to know and understanding the element of literature, especially in figurative language. The objectives of this research are (1). To identify some elements of figurative language are used by Avril Lavigne’s songs lyric. (2). To show the general meaning and detail meaning of the songs containing the figurative language itself in understanding songs lyric. (3). To find out the most and the least used figurative language of the songs. The data source used is the album self-titled Avril Lavigne by Avril Lavigne. In that album the writer chooses five songs to analyzed such as, Here’s to Never Growing Up, Bitchin’ Summer, Give You, What You Like, Hello Kitty, and Sippin’ on Sunshine. This research is descriptive qualitative research. It means that this research does not calculate the data and just gives description about figurative language that is contained in Avril Lavigne songs. It is done by using bold and underlining the songs lyric, classifying the figurative language and then giving the meaning. The result of this research is to discover some kinds of figurative language such as, Metaphor, Simile, Personification, Alliteration, Allusion, Hyperbole, Litotes, also Onomatopoeia